The Perspective View of Nurses in Ramallah Complex Hospital regards the Impact of October,7 War on Professional Duties, Economic Status, Mental and Social Wellbeing - Fatemah Yaser Mahmoud Abu Abed; Dr. Bothina Basyoni Elsayed Etewa (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
The October 7, 2023, conflict between Israel and Hamas heavily impacted healthcare in the West Bank, particularly affecting nurses at Ramallah Medical Complex. They faced challenges such as increased patient loads, resource shortages, and safety threats, leading to physical and psychological distress. There is limited research on the war's effect on their well-being and professional duties. The study aims to explore nurses' perspectives on how the conflict impacted their professional roles, economic status, mental health, and social well-being, especially regarding physical and emotional safety concerns in the conflict zone. A qualitative phenomenological approach was used to explore the experiences of 50 nurses at Ramallah Medical Complex selected purposefully. Data were collected via focus groups for 40 staff and practical nurses and in -depth interviews for nursing directors, analyzed using inductive thematic analysis with the help of NVivo software for sorting the data. Ethical approval was obtained, and all participants signed informed consent. Two major themes were explored that are: (i)nursing working conditions’ hindrances and (ii) family and personal life disruptions. The study emphasized the need for institutional support. Nurses reported increased workloads, resource limitations, financial stress, and safety threats, leading to psychological distress and burnout.  The conflict highlighted the vital role of nurses but also the need for better support systems. Coping mechanisms included peer support, and personal resilience are emphasized as a helpful strategy. Improving nurses' mental health, job security, and working conditions, along with providing stabilization points and training programs for future crises are recommended.